2019
DOI: 10.1051/0004-6361/201936008
|View full text |Cite
|
Sign up to set email alerts
|

Peering at the outflow mechanisms in the transitional pulsar PSR J1023+0038: simultaneous VLT, XMM-Newton, and Swift high-time resolution observations

Abstract: We report on a near infrared, optical and X-ray simultaneous campaign performed in 2017 with the XMM-Newton and Swift satellites and the HAWK-I instrument mounted on the VLT on the transitional millisecond pulsar PSR J1023+0038. Near infrared observations were performed in fast-photometric mode (0.5s exposure time) in order to detect any fast variation of the flux and correlate them with the optical and X-ray light curves. The optical light curve shows the typical sinusoidal modulation at the system orbital pe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
(104 reference statements)
1
9
0
Order By: Relevance
“…Outflows -The bright continuous radio emission [54,135,55] and the obscuration of the disc emission lines at certain orbital phases [46] suggested that tMSPs launch outflows of plasma. The radio emission observed in the high mode is compatible with self-absorbed synchrotron emission from a compact jet, whose spectral break would be beyond the near-infrared band given the low accretion luminosity [128]. Less collimated outflows could also be launched by the propelling magnetosphere [181,182] or by the pulsar wind [56].…”
Section: The Accretion-disc Statementioning
confidence: 59%
See 2 more Smart Citations
“…Outflows -The bright continuous radio emission [54,135,55] and the obscuration of the disc emission lines at certain orbital phases [46] suggested that tMSPs launch outflows of plasma. The radio emission observed in the high mode is compatible with self-absorbed synchrotron emission from a compact jet, whose spectral break would be beyond the near-infrared band given the low accretion luminosity [128]. Less collimated outflows could also be launched by the propelling magnetosphere [181,182] or by the pulsar wind [56].…”
Section: The Accretion-disc Statementioning
confidence: 59%
“…The emergence of an additional polarised component during the flares, possibly due to Thomson scattering from ejected matter, also supported this hypothesis [138]. Flaring variability observed in the near-infrared lagged the optical variability by ∼ 10 s, and was tentatively attributed to the reprocessing of the optical emission produced close to the light cylinder by a stream of matter ejected by the system further out [128].…”
Section: The Sub-luminous Disc Statementioning
confidence: 61%
See 1 more Smart Citation
“…Ambrosino et al (2017) report observations of optical pulsations of J1023 in its AP state, originating from inside the magnetosphere, and the flickering behaviour seen in the AP state is observed to occur simultaneously in optical and X-ray wavelengths (Papitto et al 2019). Near-infrared flaring is also seen (Baglio et al 2019). Lastly, pulsed X-ray and UV emission has been detected (Jaodand et al 2016(Jaodand et al , 2021.…”
Section: Psr J1023+0038mentioning
confidence: 91%
“…visible in the X-ray and UV bands and occurs simultaneously (Coti Zelati et al 2018;Papitto et al 2019;Jaodand et al 2021). In the optical and near-infrared bands, the low-high mode transition has never been detected, but the flaring activity is clearly visible and could be related to the emission of collimated jets or outflows (Shahbaz et al 2018;Papitto et al 2019;Baglio et al 2019). The low-high X-ray and UV mode transition is anticorrelated with the radio emission (Bogdanov et al 2018).…”
Section: Introductionmentioning
confidence: 98%